Stability Results of the Additive-Quadratic Functional Equations in Random Normed Spaces by Using Direct and Fixed-Point Method - Rani, Asha; Devi, Sushma; Antil, Manoj Kumar (Communications in Mathematics and Applications, 2023)
In this paper, we prove the Hyers-Ulam stability of different additive-quadratic functional equations in Random Normed Space (RN-Space) by direct and fixed-point method.